Los Villares de Andújar o el liderazgo de los complejos alfareros de Terra Sigillata Hispánica de origen Bético - Fernández-García, Mª Isabel (Rei Cretariae Romanae Fautorum Acta, 2022)
Roman potters’ workshops, linked to the ancient city of Isturgi (Los Villares de Andújar, Jaén, Spain), played a leading role in the production of Hispanic terra sigillata from the southern peninsular. The reconstruction of the circulation of Isturgitan products is not devoid of difficulties – especially for the first generation of potters – due to the good quality of some products, which has sometimes led us to assume erronously that they were Gallic or even Italic imports. The aim of this article is to start with the analysis of the distribution of the products of Los Villares de Andújar throughout the three generations of Hispanic terra sigillata potters documented in Isturgi – Preflavian period, Flavian period and 2nd century AD.